Kewibawaan Pelayan Khusus Penatua Dan Syamas Atas Jabatan Gerejawi Di GMIM “Kalvari” Talaitad Wilayah Tareran Dua - Ngantung, Semuel Winston (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
Seeing the life church today, many special servants do not understand the meaning of their calling as servants of God to witness and serve in the midst of the world. God to witness and serve in the midst of this world. The Christian Evangelical Church in Minahasa refers to special ministers as members of congregation who accept the call of Jesus Christ, to specifically carry out the work of church service. In contrast to want happened in the “kalvari” congregation of Talaitad Tareran Region two, the leadership of special ministers who should have shown the authority of the church in carrying out ecclesiastical offices which differed from secular positions in social life. The purpose of this study is to describe the understanding of elders and shamas about the authority of the church in service. To describe the understanding of elders and shamas about the difference between ecclesiastical and secular positions. To analyze the experience of elders and shamas in carrying out ecclesiastical office. To analyze the from of struggles by elders and shamas that hinder the carrying out of ecclesiastical office. The research method used is a qualitative method with a descriptive approach. Data collection techniques used were observation, interviews and literature study. Analyze of the data used, namely data reduction, data presentation and verification / conclusion. From the result of the research found in field of research, it turns out that the understanding of elders and shamas about the authority of the church in service has a good view and deserves to be done according to God’s will so that the congregation is able to build its faith. It turns out that the understanding of elders and shamas about the difference from ecclesiastical and secular positions lies in the responsibility to obey an authority and expected rewards. It turns out that the experience of elders and shamas in carrying out ecclesiastical offices is oriented towards giving oneself in service with sincerity and humility and the power of prayer to be a source of strength even though there are struggles of difficulty in running simultaneously with secular positions. It turns out that the from of struggles that hamper in carrying out ecclesiastical positions tend to be those who are unable to manage their time and personal desires to achieve success and lack of support from families and congregations especially suffer from health problems but there is an awareness to be able to change themselves and their service duties in the future.